Strategy to modernize the classical Malay prose from generative transformation perspective - Makmun, Rozaiman; Abu Bakar, Roslina; Pengiran Omar Ali Shaiffuddin, Dk Soraya; Madin, Abu Bakar (Human Resource Management Academic Research Society, 2022)
One of the components and teaching material that exists in the Malay Language subject in Brunei Darussalam is modernizing classical Malay prose. This component is taught and produced in the middle to pre-university level examinations. Students always face difficulties in switching classical Malay language (CML) to modern or standard Malay language (MML). One of the reasons of this is due to the hardship of understanding meaning and sentence structure that are convoluted and inverted as well as the existence of words or terms that are no longer used in the current or modern Malay language. Therefore, this study is executed for the purpose of exploring strategies that are used by two students when modernizing classical Malay prose. The process of modernizing will be explored through the Generative Transformation (TG) theory. The framework of the study uses the qualitative approach and data is collected using the triangulation method that combines observation, interviews and document analyses. This case study only chooses two students of Year 10 as study participants in a secondary school in the Brunei and Muara districts. The choosing of excellents students and weak students is to make comparisons from the aspect of the strategies that are practiced. The study data is analysed thematically based on the literature theme in the TG writing and perspective field. The outcomes of the study show that excellent students are more inclined towards using more of TG elements in comparison to weak students. The implication of the study has potential for guidance to develop learning and facilitation that is more effective in modernizing classical Malay prose.